Microdiversity sustains the distribution of rhizosphere-associated bacterial species from the root surface to the bulk soil region in maize crop fields - Fu, Xianheng; Fu, Qi; Zhu, Xiaozheng; Yang, Xian; Chen, Huaihai; Li, Shiqing (Frontiers in Plant Science, 2023)
Over the years, the microbial community of maize (Zea mays) rhizosphere has been extensively studied; however, the role of microdiversity sustain rhizosphereassociated microbial species distribution from root surface to bulk soil in mature maize is still unclear. Although operational taxonomic units (OTUs) have been used to classify species, amplicon sequence variants (ASVs) have been shown to be effective in representing microdiversity within OTUs at a finer genetic scale. Therefore, the aim of this study was to examine the role of microdiversity in influencing the distribution of rhizosphere-associated microbial species across environmental gradients from root surface to bulk soil at the OTU and ASV levels. Here, the microbial community structures of bulk, loosely bound, and tightly bound soil samples from maize rhizosphere were examined at OTU and ASV levels. The results showed that OTU and ASV methods exhibited similar microbial community structures in rhizosphere.Additionally, different ecotypes with varying distributions and habitat preferences were observed within the same bacterial OTU at the ASV level, indicating a rich bacterial microdiversity. In contrast, the fungal community exhibited low microdiversity, with no significant relationship between fungal microdiversity and persistence and variability. Moreover, the ecotypes observed within the bacterial OTUs were found to be positively or negatively associated with environmental factors, such as soil organic carbon (SOC), NO3--N, NH4 ＋ -N contents, and pH. Overall, the results showed that the rich microdiversity could sustain the distribution of rhizosphere-associated bacterial species across environmental gradients from root surface to bulk soil. Further genetic analyses of rhizosphere-associated bacterial species could have considerable implications for potential mediation of microdiversity for sustainable crop production.